Hope, quality of life, and self-efficacy among mothers with special needs children - Ayesha Rasheed (INSPIRA: Indonesian Journal of Psychological Research, 2022)
This research aims to find out the level of hope, self-efficacy, and quality of life of mothers with special needs children. There has been very little research on mothers’ health of special needs children and there was a significant gap that needed to be addressed. A correlational research design was used with purposive sampling of 30 mothers (N=30) from Amin-Maktab Institute Outreach Program, Lahore, Pakistan, who were involved in this study. A series of questionnaires as the quality of life, hope scale, and self-efficacy scale was administered to mothers after taking consent. Correlation and independent-sample t-tests were used to analyze data. Results revealed that standards/physical health (domain 1) has a strong relationship with hope/pathways (domain 2) with a 0.56 level of significance. Standards (domain 1) and pleasures/social (domain 3) have a strong relationship with 0.42 but there is a difference in the mean between mothers of boys and mothers of girls. The environment affects the physical, psychological, and social health of mothers with special needs children. While mothers with a higher level of hope have a higher quality of life and high self-efficacy leads to high physical health among mothers. Research conclusion specifies that mothers of intellectually disabled boys have had a higher level of hope and pleasure (social relationship) than mothers of girls